The tobacco-using periodontal patient: The role of the dental practitioner in tobacco cessation and periodontal diseases management - Chaffee, Benjamin W. (Periodontol 2000, 2016)
Although the prevalence of tobacco use has declined in some parts of the world, tobacco use remains a persistent and, in some cases, growing problem that will continue to be a fundamental challenge facing dental practitioners in the decades ahead. The dental practitioner has a unique opportunity and professional obligation to be a positive influence in reducing the economic and social burden inflicted by tobacco use on dental and general health. In this article, the current non-invasive, evidence-based approaches are presented for the dental practitioner to help patients avoid tobacco initiation, to encourage and assist patients’ in tobacco cessation, and to address tobacco-induced damage to periodontal supporting tissues.